THEMATIC AND VISUAL ANALYSIS OF THE SHORT FILM “MANIPULATOR” AS A FORM OF COMMENTARY ON SOCIAL DYNAMICS - Putu Eka Kharisma Dewi; Peter Wayan Minheere; Putu Chrisma Dewi; Putu Chris Susanto (LPPM Universitas Dhyana Pura, 2022)
ABSTRAKThe purpose of this study is to analyze how short films may become forms of media that raise and comment on controversial issues in society. The authors used descriptive analysis to analyze an Indonesian short film titled